Supersymmetric AdS(5) solutions of type IIB supergravity - Gauntlett, J; Martelli, D; Sparks, J; Waldram, D (2006)
We analyse the most general bosonic supersymmetric solutions of type IIB supergravity whose metrics are warped products of five-dimensional anti-de Sitter space (AdS5) with a five-dimensional Riemannian manifold M5. All fluxes are allowed consistent with SO(4, 2) symmetry. We show that the necessary and sufficient conditions can be phrased in terms of a local identity structure on M5. For a special class, with constant dilaton and vanishing axion, we reduce the problem to solving a second-order nonlinear ODE. We find an exact solution of the ODE which reproduces a solution first found by Pilch and Warner. A numerical analysis of the ODE reveals an additional class of local solutions giving complete metrics on S5 but with three-form flux and Killing spinors that are not globally defined. © 2006 IOP Publishing Ltd.